PRAAT VISUALIZATION AND X-BAR THEORY IN CONTROVERSIAL SPEECH OF BASUKI TJAHAJA PURNAMA (VISUALISASI PRAAT DAN TEORI X-BAR DALAM UJARAN KONTROVERSIAL BASUKI TJAHAJA PURNAMA) - Wido Hartanto; Kundharu Saddhono; Ady Dwi Achmad Prasetya; Ku Ares Tawardoloh (Universitas PGRI Sumatera Barat, 2021)
Language is a means of interaction in social life. In the process of social interaction related to language use, there are often unpleasant things, such as expressions of anger, hatred, threats, cursing, cursing, and even harassment. This becomes a problem when such expressions are conveyed in public spaces. One of the interesting cases related to public speaking is the controversial speech case of Basuki Tjahja Purnama (BTP). The case of the BTP speech is linguistically interesting to study because it involves hot religious issues in Indonesia. BTP's controversial speech became a polemic because it was delivered in front of the wider community. This study reveals the controversial expressions of BTP using Praat and X-Bar Theory. The data from this study were controversial BTP speech recordings and BTP speech transcripts. This research data collection method using literature study. Data in the form of records will be broken into several parts. then the recorded data is also transcribed. The method of data analysis used the split method because the determining tools were in the language itself. The data analysis technique uses the comparative to equalize. Pratt was chosen because it is able to show pitch, intensity, formant and spectogram levels. Praat became an instrument for analyzing BTP's controversial speech recordings. This provides forensic evidence whether the speech contains speech that promotes hate speech. Based on the results of Praat's analysis, it is known that BTP utterances experience a certain emphasis when discussing issues or problems that concern him, especially those related to religion. Furthermore, X Bar Theory was used to analyze transcripts of BTP's controversial utterances. The X Bar theory is an analytical tool about the meaning of BTP speech. X Bar focuses on the core processes of lexical constituents in three domains, namely argument, complement and determinants. Based on the analysis of the X Bar theory, it is known that BTP's controversial expressions are aimed at certain parties. This is demonstrated by the emphasis on the argument domain.